Effects of the inclination angle on natural convection heat transfer and entropy generation in a square porous enclosure. (1st December 2016) - Meshram, Prashant; Bhardwaj, Saurabh; Dalal, Amaresh; Pati, Sukumar
ABSTRACT: In this paper, we analyze numerically the effects of the inclination angle on natural convection heat transfer and entropy generation characteristics in a two-dimensional square enclosure saturated with a porous medium. There is a significant alteration in Nusselt number with the orientation of the enclosure at higher values of Rayleigh number. It reveals that the variation of entropy generation rate with the inclination angle is significant for higher values of Darcy number. The dominant source of irreversibility is due to heat transfer at low values of Darcy number, whereas entropy generation due to fluid flow dominates over that due to heat transfer for larger values of Darcy number.